Cross Culture and Faith : The Life and Work of James Mellon Menzies - Dong, Linfu, 1961- (Book collections on Project MUSE., 2005)
James Mellon Menzies (1885-1957) was a Canadian engineer, Presbyterian missionary, and archaeologist active in China in the 1920s and 1930s. In a tradition that saw archaeology as a means of gathering artefacts for the collections of Western museums, Menzies believed in collecting for the people of China. He also saw his archaeological work as an extension of his missionary work, connecting, through his discoveries, the religious beliefs of ancient China to those of evangelical Christianity. In Cross Culture and Faith, Linfu Dong sheds new light on the modern encounter between China and the West through Menzies's life, work, and thought. He elucidates the difficult 'negotiation' processes that Menzies endured on multiple levels and with multiple forces, including Chinese nationalism, Western imperialism, the evangelical Mission, and his own personal interest in Chinese archaeology within that world. Despite his belief in assuring Chinese artefacts remained in China, some of Menzies's personal collection was donated to the Royal Ontario Museum in Toronto and to the Art Gallery of Greater Victoria in British Columbia. This has assured his place in the cultural memory of both East and West - appropriate, since his life so often straddled the two worlds.